Perfect likeness : photography and composition - Ferguson, Russell (London : Delmonico Books, 2014)
"The exhibition will be accompanied by a fully-illustrated, 128-page catalogue with an essay by the curator Russell Ferguson, short biographies for the 24 artists featured in the exhibition, and a complete exhibition checklist. In the essay, Ferguson discusses the rise and fall of the pictorial in photography in the early 20th century and how the spontaneous style of street photography came to dominate the medium, before looking at the return of considered composition from the late 1970s onward. Often quoting the artists in the exhibition, and describing their very deliberate processes for making pictures, Ferguson traces this tendency in contemporary photography. He articulates the conceptual goals of the work and positions in in a wider context. Designed by Lorraine Wild/Green Dragon and edited by Jane Hyun, the catalogue will feature full-color reproductions of the 53 works in the exhibition as well as 20 comparative images cited in Ferguson's essay"--
Includes bibliographical references.
Keywords: Composition (Photography); PHOTOGRAPHY / Subjects & Themes / General; PHOTOGRAPHY / Collections, Catalogs, Exhibitions / Group Shows